Design and implementation experience of a didactic sequence based on the genre-based approach for the improvement of writing skills in a B2 level student group (2024)
Writing stands as one of the most complex and demanding skills in the process of learning English as a second language. It is especially challenging for those seeking academic or professional opportunities. This research focuses on recounting the experience of designing and implementing a didactic sequence based on the genre-based approach, with the aim of improving the writing competence in a group of B2-level students at a language institute in Cali, Colombia. The information gathered came from two writing activities developed at the start (pre-test) and after the intervention with the sequence (post-test). These productions were analyzed using the same criteria to evaluate the students' progress in this skill. In summary, a substantial improvement in the students' ability to write in English was observed. This progress was attributed to the detailed conceptualization of the literary genre explored (personal statement), which sparked significant interest among the students considering its importance in academic and professional contexts, as well as a great deal of exposure to various practical writing activities within the didactic sequence contributing to the delivery of a final composition task